Organizational Factors Affecting Lecturer Performance in HEIs in the Context of Blended Learning: An Empirical Study in Vietnam - Nguyen Thi Thuy Hanh (Ali Khorsandi Taskoh, 2023)
This study is an attempt to investigate the influence of organizational factors, including institutional policies, work environment, infrastructure, and workload on the performance of lecturers in Vietnamese higher education institutions. Performance was tested to measure their effectiveness as well as discover important variations between particular groups. This empirical study follows a quantitative approach based on the collection of authentic data through questionnaires from 200 lecturers affiliated with 10 higher education institutions in Vietnam. All quantitative data were placed in a comprehensive database and processed by using Statistical Package for the Social Science software. The study's key findings suggest that factors significantly influencing lecturer performance include training, performance evaluation, salary (institutional policies); colleague support, feedback on performance, organizational communication (work environment); furniture and computer technology (infrastructure); doing research, teaching and testing, and blended course designing (workload). The performance of lecturers is found to be unaffected by the other components in a substantial way, namely incentives, leadership, noise and light, community service. The results of the research output measurement showed that lecturers lacked research abilities. A number of managerial implications are then discussed with an aim of enhancing the performance of lecturers in higher education institutions.